Is density of neighbourhood restaurants associated with BMI in rural Chinese adults? A longitudinal study from the China Health and Nutrition Survey - Du, Wenwen (BMJ Publishing Group, 2014)
OBJECTIVES: The neighbourhood availability of restaurants has been linked to the weight status. However, little is known regarding the relation between access to restaurant and obesity among the Chinese population. This study aims to explore the relationship between neighbourhood restaurant density and body mass index (BMI) in rural China. DESIGN: A longitudinal study using data from the China Health and Nutrition Survey (CHNS) was conducted. Participants aged 18 and older from the 2004, 2006, 2009 and 2011 CHNS were recruited Separate sex-stratified random intercept-slope growth models of repeated BMI observations were estimated in the study. SETTING: The data were derived from rural communities in nine provinces in China. PARTICIPANTS: There were 11 835 male and 12 561 female person-years assessed in this study. OUTCOMES: The primary outcome of this study was weight status. It is defined as a BMI value, a continuous variable which is calculated by dividing weight (kg) by the square of height (m(2)). RESULTS: The study indicated that among men an increase of one indoor restaurant in the neighbourhood was associated with a 0.01 kg/m(2) increase in BMI, and an increase of one fixed outdoor food stall was associated with a 0.01 kg/m(2) decrease in BMI, whereas among women, an increase of one indoor restaurant in the neighbourhood was associated with a 0.005 kg/m(2) increase in BMI, and an increase of one fast-food restaurant and one fixed outdoor food stall was associated with a 0.02 and 0.004 kg/m(2) decline in BMI, respectively. CONCLUSIONS: The density of neighbourhood restaurants was found to be significantly related to BMI in rural China. The results indicated that providing healthy food choices and developing related public health policies are necessary to tackle obesity among rural Chinese adults.